Colombia: An enviroment of credibility: a key element for effective action (2001)
ABSTRACT: The autor is a member of the Effectiveness Initiative (EI) team in Colombia that is investigating effectiveness in the Proyecto de Mejoramiento Educativo, de Salud y del Ambiente (PROMESA), a community mobilisation Project that began 25 years ago on the isolated Pacific coast of Colombia. PROMESA was operated from 1977 to 1998 by Centro Internacional de Eduacuión y Desarrollo Humano (CINDE), a non-governmental organisation (NGO) that carries out social, educational. And human development Project focused on the healthy development of children. From 1998, the Project was operated by Centro de Investigaciones para el Desarrollo Autosostenible Local (CIDEAL), an NGO of local personne that supports community processes. In participating in the EU, stakeholders in PROMESA saw that it was important to find out what people consider to have been effective, and how their perceptions have changed ovr the years. EI work in the Project consisted of a study that was carried out with participants in the PROMESA Project; advisers of CINDE and of CIDEAL; other organisations with which PROMESA has coordinated activities; municipalities and children and mothers who have used the project’s services. The central question of the study was: “What lessons have been learned during the life of the Project?”. This article draws on that study to discuss what is now seen as the key importance of credibility to the effectiveness of the Project, showing its relationship with other important elements that have been identified in the process of validating the information that the study is producing.